PENGARUH KEGIATAN MAGANG DU/DI DAN PENGALAMAN ORGANISASI TERHADAP EMPLOYABILITY SKILLS MAHASISWA PENDIDIKAN AKUNTANSI - Levia Melati; Siswandari Siswandari (Universitas Sebelas Maret, 2025)
AbstractThis study aims to determine (1) the effect of Internship program in business/industry on employability skills; (2) the effect of organizational experience on employability skills; (3) the effect of Internship program in business/industry and organizational experience on students' employability skills. The method used in this study is a quantitative method. The sample in this study were 106 students of the Accounting Education Study Program, batch 2021 and 2022, at a university in Surakarta. The sampling technique used simple random sampling. Data collection was carried out by distributing questionnaires. The analysis used was multiple linear tests. The results of the study showed that: (1) there is an influence but not significant between Internship program in business/industry on employability skills. This is shown by the significance value in the t-test of 0.095 (p > 0.05). (2) there is a significant influence of organizational experience on employability skills. This is shown by the significance value in the t-test of 0.000 (p < 0.05). (3) There is a significant influence of Internship program in business/industry and organizational experience on employability skills with a significance value in the F-test of 0.000 (p < 0.05).Keywords: Internship program in business/industry, Organizational experience, Employability skills.AbstrakPenelitian ini bertujuan untuk mengetahui (1) pengaruh kegiatan magang Du/Di terhadap employability skills; (2) pengaruh pengalaman organisasi terhadap employability skills; (3) pengaruh kegiatan magang Du/Di dan pengalaman organisasi terhadap employability skills mahasiswa. Metode yang digunakan dalam penelitian ini ialah metode kuantitatif. Sampel pada penelitian ini adalah mahasiswa Program Studi Pendidikan Akuntansi angkatan 2021 dan 2022 sebanyak 106 mahasiswa salah satu perguruan tinggi di Surakarta. Teknik pengambilan sampel menggunakan simple random sampling. Pengumpulan data dilakukan dengan penyebaran kuesioner. Analisis yang digunakan adalah uji linier berganda. Hasil penelitian menunjukkan bahwa: (1) terdapat pengaruh namun tidak signifikan kegiatan magang Du/Di terhadap employability skills. Hal ini ditunjukkan nilai signifikansi pada uji t sebesar 0,095 (p > 0,05). (2) terdapat pengaruh signifikan pengalaman organisasi terhadap employability skills. Hal ini ditunjukkan dengan nilai signifikansi pada uji t sebesar 0,000 (p < 0,05). (3) terdapat pengaruh signifikan kegiatan magang Du/Di dan pengalaman organisasi terhadap employability skills mahasiswa dengan nilai signifikansi pada uji F 0,000 (p < 0,05). Kata Kunci: Kegiatan Magang Du/Di, Pengalaman Organisasi, Employability Skills